2020
DOI: 10.1371/journal.pone.0243473
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hepatocellular carcinoma occurrence after HCV eradication in patients without cirrhosis or with compensated cirrhosis

Abstract: The present study aimed to investigate the incidence of hepatocellular carcinoma (HCC) and factors related to HCC occurrence after direct-acting antiviral (DAA) treatment in the Fukushima Liver Academic Group (FLAG). We conducted a multicenter retrospective cohort study of 1068 patients without cirrhosis (NC) or with compensated liver cirrhosis (LC) who achieved a sustained virologic response (SVR). First, we compared the cumulative HCC incidence and survival rates in NC (n = 880) and LC (n = 188) patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…Finally, 5 authors reported data on patients with advanced fibrosis, defined through histology (F3-F4), non-invasive tests or criteria for chronic advanced liver disease (cACLD) 11 , 36 , 43–46 ( Table 2 ). Eight out of these studies enrolled only patients with an SVR, 10 , 21 , 30 , 33 , 37 , 44–46 whilst in one study data could be extrapolated. 34 In studies including also non-SVR patients, rates of treatment failure ranged between 1.9% and 10% ( Table 2 ).…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, 5 authors reported data on patients with advanced fibrosis, defined through histology (F3-F4), non-invasive tests or criteria for chronic advanced liver disease (cACLD) 11 , 36 , 43–46 ( Table 2 ). Eight out of these studies enrolled only patients with an SVR, 10 , 21 , 30 , 33 , 37 , 44–46 whilst in one study data could be extrapolated. 34 In studies including also non-SVR patients, rates of treatment failure ranged between 1.9% and 10% ( Table 2 ).…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
“…In F3-F4 patients, Alonso Lopez et al found that both baseline FIB-4 >3.7 and FIB-4 >3.3 one year after treatment were associated with de-novo HCC 45 ( Table 7 ). Other NITs had been investigated as predictors of HCC in several studies: the albumin-bilirubin (ALBI) score grade 2–3 29 , 37 , 42 and AST to platelet (PLT) ratio index (APRI) >2.5 11 emerged as independent risk factors for de-novo HCC in patients with cirrhosis and advanced fibrosis, respectively.…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
See 3 more Smart Citations